EFFECTS OF TRANEXAMIC ACID IN THE WIDE RECONSTRUCTIVE SURGERY ON HIP JOINT - T. A. Zhirova; E. B. Makarova; V. A. Rudnov (Вестник анестезиологии и реаниматологии, 2017)
The wide surgery on hip joint is followed by the blood loss, local and systematic inflammatory response. Tranexamic acid is widely used in surgery for conservative homeostasis and its anti-inflammatory effect is also well known. The purpose: to justify the dosing regimen of tranexamic acid from the position of minimum blood loss and inflammatory response. Materials and methods: 32 patients from the control group received standard therapy with tranexamic acid at the dose of 20 mg/kg intravenously twice a day: 30 minutes prior to the surgery and in 6 hours since the 1st administration; in the main group (29 patients) the standard regimen was supplemented by intra-operative administration – 10 mg per kg-1 ∙ h-1. Results. The volume of the intra-surgery, drainage, general and estimated peri-operative blood loss was not statistically different between two groups. The level of pro-inflammatory and anti-inflammatory cytokines was higher in the drainage blood compared to the peripheral one (p < 0.001). The concentration of soluble receptors to IL-6 and FNO-α was statistically and clinically confidently higher in the control group compared to the main one at the majority stages of the study (p < 0.05). Conclusion. Tranexamic acid possesses anti-inflammatory action regardless of the dose.